Topical timolol for superficial cutaneous infantile hemangiomas in very preterm infants - Matić, Aleksandra; Prćić, Sonja; Matić, Milan (Vojnosanitetski pregled, 2021)
Introduction. Infantile hemangiomas (IHs) occur 3 to 4 times more frequently in preterm infants than in those born at term. Yet, data about efficacy and safety of topical therapy for IHs in preterm infants, especially in those born with very low gestational age (less than 33 gestational weeks) is very scarce. Case report. We reported five very preterm girls treated with topical timolol maleate 0.5% gel for superficial cutaneous IHs. In four infants topical timolol was applied on a single IH each, and in one infant two IHs were treated. Out of six treated IHs, one was located on the face, four on the trunk and one on the leg. They were regularly monitored for IH involution and potential adverse effects of timolol for 6–13 months of local treatment. Good therapeutic effect was achieved in all the presented infants, with no adverse effects related to topical administration of timolol-maleate. Conclusion. Topical timolol is an effective and safe therapy for superficial cutaneous infantile hemangiomas in very preterm infants. The treatment should be discussed in detail with parents and individualized management plan should be tailored for each infant in order to maximize the chances of a successful outcome, while avoiding adverse effects.
Keywords: hemangioma; skin neoplasms; timolol; administration, topical; child; infant, premature; treatment, outcome.